A fine grained aspect coordination mechanism - Zambrano Polo y La Borda, Arturo Federico; Gordillo, Silvia Ethel; Fabry, Johan (2010)
Aspect interactions and conflicts are an important issue for AOSD. Aspectual conflicts are difficult to manage and, specifically semantic ones remain an open issue for AOSD. In this work, we present a simple mechanism for handling semantic conflicts at the granularity of aspect and advice in the resource awareness domain. We also analyse the impact of such coordination mechanism on some important properties of software (some of the so called ilities). We found that aspects can effectively be coordinated and remain independent, improving their reusability, modularity and evolvability.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Journal of Software Engineering and Knowledge Engineering, 20(7), pp.1025-1042
Keywords: SEMÁNTICA